Hubungan Pengetahuan Kesehatan Gigi dan Mulut dengan Karies Gigi pada Mahasiswa Baru Fakultas Kedokteran Gigi Universitas Jember Tahun Akademik 2016/2017 (Correlation of Oral Health Knowledge with Dental Caries in First Grade Dentistry Students of Jember - Galuh Cita Sari Rahtyanti; Hestieyonini Hadnyanawati; Erawati Wulandari (UPT Percetakan dan Penerbitan Universitas Jember, 2018)
Background: One of major oral health problem found in oral cavity is dental caries. Several factors can induce dental caries such as economical factors, excessive high sugar content foods consumption, and neglect of oral hygiene due to lack of knowledge in how important is teeth and mouth maintenance. Objective: To analyzed correlation between oral health knowledge and dental caries in first grade Dentistry students of Jember University Academic Year 2016/2017. This research used cross sectional approach with total respondents of 119 students. The assessment of oral health knowledge was done by questionnaire and DMF-T index was used to evaluated dental caries in oral cavity. Results and Conclusion: The majority of oral health knowledge distribution in first grade dentistry students of Jember University academic year 2016/2017 was 106 students (89,1%) in good category and DMF-T score of 53 students or 44.5% in very high category.The results of data analyzed by Spearman correlation test could be concluded that there was a significant relation between dental caries and oral health knowledge of first grade Dentistry students Jember University academic year 2016/2017 with moderate correlation strength (-0.460). Keywords : Dental caries, First grade dentistry students, Oral health knowledge